WEBSITE DEVELOPMENT PROJECT FOR KAMPUNG SANTRI, INDONESIA - Azri Syafiq Bin Md Julis; Fadillah Binti Ismail; Muhammad Izzad Bin Luqman (Jurnal Penyelidikan Sains Sosial, 2020)
This study is a project base to develop a website as promoting and communicationtool for residents of kampung Santri, Indosnesia. This study has applied a combination ofquantitative and qualitative methods in obtaining data through the distribution ofquestionnaires, interviews and observations. Facing the challenge of industry revolution 4.0,Internet of Things, artificial intelligence and robotic become a new initiative to replace manpower. A confused mind on these days will make future generation become uncompetitiveregarding uses of technology. Therefore, this study is an effort by UTHM and UniBantenstudents through project under Real Work Lecture (KUKERTA) in ensuring community abilityand mastering technology so that the residents of Kampung Santri can function effectively andnot left behind in the twenty-first century.